The Great Mother Archetype of a Character in Turning Red (2022) Film - Maharani, Silvia; Amelia, Dina (Universitas PGRI Madiun, 2024)
This study investigates the portrayal of Carl Jung's Great Mother Archetype in the Disney-Pixar film Turning Red (2022), focusing on the character Ming Lee. As a literary medium, film was often used to communicate moral values explicitly. The researcher employed a descriptive qualitative method and identified six scenes that depicted the Great Mother archetype, such as Ming scolding a convenience store guard, Mei’s first transformation into a red panda, secretly monitoring Mei, controlling the red panda, the battle with the giant red panda, and the reconciliation with her mother in the spirit world. The study concluded that Ming Lee's over-controlling nature consistently represented the Great Mother archetype, where excessive control negatively impacted the growth of other characters.